THE ADEQUACY OF CPAs’ UNDERSTANDING OF THE RELATIVE SERIOUSNESS OF ALPHA AND BETA RISKS IN STATISTICAL AUDIT SAMPLING - Bambang Sudibyo (Faculty of Economics and Business, Universitas Gadjah Mada, 2000)
The issue raised in this article is the adequacy of US CPAs' understanding of the relative seriousness of alpha and beta risks in statistical audit sampling. The objective of this study is to seek empirical evidence on the issue. Empirical data was collected in 1984 using the method of mail survey, with members of the American Institute of Certified Public Accountants (AICPA) serving as the target population. The author concluded that CPAs, in general, did not have an adequate understanding of the relative seriousness of alpha and beta risks in statistical audit sampling. The author also concluded that the understanding of the issue differed across various groups of CPAs. Big eight CPAs, in general, had an adequate understanding of the issue, while CPAs of the other groups, in general, did not. Comparisons between the scores of these groups Indicate that 1) big-eight CPAs scored higher than non-big-eight CPAs; 2) academic CPAs scored higher than non-academic CPAs; and 3) contrary to expectation, practitioners in general did not score significantly higher than non-practitioners.